PENGARUH TRANSACTIONAL LEADERSHIP TERHADAP KEPUASAN KERJA DENGAN MEDIASI MOTIVASI PADA ANGGOTA POLRES PAMEKASAN - Bambang Wijaya; Diah Nartasari (Fakultas Ekonomi Universitas 45 Surabaya, 2017)
Leaders are required to be able to influence subordinates in carrying out an order without coercion so that subordinates/members will voluntarily work according goals as directed by the leader of the institution. Transactional Leadership is developed based on the level of human needs such as rewards, promotions or other awards. The leaders in Transactional Leadership tend to be more passive because he/she has gave full authority to subordinates in carrying out the tasks. Motivation is developed from the theory of Clelland covering Achievement Motivation, Affiliation Motivation, Competence Motivation and Power Motivation. These four things are some forms of motivation which determines the pattern of the motivation of members of the organization. Job satisfaction is the emotional stage of the subordinates/members which happened or not will concern about the meeting point between the remuneration that they expected compared to what they have received. In various studies variables Transactional Leadership, Motivation and Job Satisfaction were found to have a close relationship each other and this study is to combine those variables into a model and tested to further clarify the pattern of the relationship between these three variables. The object of this quantitative research is a working unit region in East Java Province, Pamekasan Police Department. Sampling technique that being used is non-probability sampling. The type of method of this research is purposive sampling. The sample were 89 respondents, for those who served as members of the police and civil workers in Pamekasan Police Department. Data were collected using a questionnaire. The analysis technique used is regression analysis with SPSS software. The analysis showed that the variables Transactional Leadership is having effect on job satisfaction when mediated by Motivation variable.